Identification of overtraining in well-trained runners using the lactate/RPE ratio - Campbell, A. R.; Potteiger, J. A. (Medicine & Science in Sports & Exercise, 1999)
It has been proposed that a decrease in the lactate/RPE ratio is a useful indicator of overtraining in endurance athletes. Well-trained runners (N = 14) trained for 12 weeks. Ss performed an incremental exercise to exhaustion at weeks 0, 4, 8, and 12. The ratio was determined by dividing lactate concentration by RPE and multiplying the result by 100. Training volume and intensity were monitored over the period of the investigation. Training volume was significantly greater during the first four weeks compared to the latter two periods. The ratio was higher in the first and second four-week periods compared to the final stage. Race pace for 5 km and 8 km significantly decreased baseline to week 4 and then did not change. There were no significant differences in maximal aerobic power among the measurement/training periods. Implication. The lactate/RPE ratio was not sensitive at these relatively low exercise intensities and does not appear to be useful for monitoring overreaching or overtraining.